The Effect of Varying Thawing Temperatures and Preserving Conditions on the Recovery Rate of Cryopreserved Equine Dendritic Cells - Deeb, Tarek; Schwebel, Felix; Rittinghaus, Tim; Glasmacher, Birgit (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):283